Bariatric and Metabolic Surgery : Indications, Complications and Revisional Procedures - Angrisani, Luigi (Springer Milan : Imprint: Springer, 2017)
This book describes the surgical bariatric procedures most frequently performed worldwide and examines their evolution in recent years both within Italy and internationally. For each operation, indications, the surgical technique, potential complications, and the outcomes with respect to weight and obesity-associated comorbidities are presented. In view of the significant failure rate revealed by studies on the long-term results of bariatric surgery, the problem of weight regain and revision surgery are also discussed in detail, covering the different types of revision, conversion to other procedures, and the main outcomes. In addition, individual chapters focus on selected topics of importance. The role of bariatric surgery in the cure of type 2 diabetes ("diabetes surgery") is discussed and the debate over the significance of gastroesophageal reflux disease and hiatal hernia for choice of procedure is summarized. Finally, the most common endoluminal procedures, which have been gaining in importance, are described and other bariatric operations, outlined.
Keywords: Medicine.; Diabetes.; Gastroenterology.; Metabolic diseases.; Surgery.; elektronické knihy; electronic books